2024
DOI: 10.1021/acsaem.4c00307
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic High-Efficiency Photoelectrochemical Water Splitting via Type-II Heterojunction MW:BVO/CeO2 Coupled with Ultrathin NiFeOOH

Lei Ding,
Lin Wang,
Shuai Chu
et al.

Abstract: In order to solve the problem of slow water oxidation kinetics and charge complexation of the BiVO 4 photoanode, CeO 2 octahedral nanomaterials doped with different amounts of NaH 2 PO 4 (COP3) were synthesized by a hydrothermal method in one step. CeO 2based materials have been widely studied in the fields of organic catalysis, photocatalysis to decompose water, and photodegradation of organic pollutants, showing excellent photocatalytic properties. The heterostructure formed by MW:BVO and COP3 (doped with 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…To overcome this problem, the earlier heterostructuring strategy with In 2 O 3 is adopted. A Type-II heterostructure is formed, which delays the charge-carrier recombination and the activity in PEC water splitting reaction is enhanced. Earlier, our group reported that the In 2 S 3 /In 2 O 3 nanopyramid heterostructures have enhanced light absorption, a reduced photoinduced charge carrier recombination rate, and improved charge collection . Furthermore, the efficiency of In 2 S 3 /In 2 O 3 nanopyramid heterostructures can be enhanced if the optical absorbance and charge carrier generation can be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, the earlier heterostructuring strategy with In 2 O 3 is adopted. A Type-II heterostructure is formed, which delays the charge-carrier recombination and the activity in PEC water splitting reaction is enhanced. Earlier, our group reported that the In 2 S 3 /In 2 O 3 nanopyramid heterostructures have enhanced light absorption, a reduced photoinduced charge carrier recombination rate, and improved charge collection . Furthermore, the efficiency of In 2 S 3 /In 2 O 3 nanopyramid heterostructures can be enhanced if the optical absorbance and charge carrier generation can be tuned.…”
Section: Introductionmentioning
confidence: 99%